Investigation of the effect of amino acid chirality in the internucleoside linker on DNA:DNA and DNA : RNA duplex stability - Seema Bagmare; Gunjal, Anita D.; Kumar, Vaijayanti A. (Tetrahedron, 2015)
Enzymatically and chemically stable amide-linked di/oligonucleosides are highly desired synthetic targets in which the phosphodiester linkages in native DNA are replaced by amide linkers of appropriate length and stereochemistry. The five-atom amide-linked dimers, synthesized from 3'-amino-3'-deoxy thymidine, (alpha-(L/D) proline/prochiral glycine and thymidine/uridine-4'carboxylic acid derivatives, were incorporated into the DNA backbone to achieve partial replacement of selected phosphodiester linkages. The results stressed the importance of the chirality of linker amino acid. D-Proline was found to be the most compatible as an internucleoside linker in the DNA backbone to stabilize the complexes with DNA or RNA as compared to L-proline and glycine. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: alpha-Amino acid; Chiral amide linkage; DNA; Five-atom amide linkage; L/D-Proline

Inhibition of miR-21 by 3 `/5 `-serinyl-capped 2 `-O-Methyl RNA Interspersed with 2 `-O-(2-Amino-3-Methoxypropyl) uridine units - Nahar, Smita; Kotikam, Venubabu; Kumar, Vaijayanti A.; Maiti, Souvik (Nucleic Acid Therapeutics, 2016)
miRNAs are highly conserved class of small ncRNAs whose involvement in human pathophysiologies is extensively investigated. MiR-21 is a well established oncogenic miRNA whose deregulation plays a significant role in onset and progression of cancer. The need of novel approaches to downregulate miR-21 is rapidly expanding. Potent inhibition of miR-21 is achieved by chemically modified 2-O-methyl RNA oligonucleotide. The serinol capping at 3 and 5ends and the interspersed 2-O-(R-2-amino-3-methoxypropyl) uridine units enhance the nuclease resistance and efficacy of 2-O-methyl RNA for the inhibition of miR-21. This represents a simple and novel modification for developing oligonucleotide-based therapeutics.
Keywords: antagomirs; cancer; microRNA; noncoding RNA; oligonucleotides

Influence of fluorine substitution on the molecular conformation of 3 `-deoxy-3 `-fluoro-5-methyluriaine - Aher, Manisha N.; Erande, Namrata D.; Kumar, Vaijayanti A.; Fernandes, Moneesha; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2020)
{Fluorine substitutions on the furanose ring of nucleosides are known to strongly influence the conformational properties of oligonucleotides. In order to assess the effect of fluorine on the conformation of 3'-deoxy-3'-fluoro-5-methyluridine (T-R(F)), C-10 H13FN2O5, we studied its stereochemistry in the crystalline state using X-ray crystallography. The compound crystallizes in the chiral orthorhombic space group P2(1)2(1)2(1) and contains two symmetry-independent molecules (A and B) in the asymmetric unit. The furanose ring in molecules A and B adopts conformations between envelope (E-2, 2'-endo
Keywords: crystal structure; fluoro nucleoside; pseudorotation parameter; sugar puckering; uridine

Implications of natural 3′-5′- linkages in the loop region of isomeric 2′-5′-linked thrombin-binding aptamer - Aher, Manisha; Kumar, Vaijayanti A.; Fernandes, Moneesha (Chemistryselect, 2024)
The backbone modification of the thrombin-binding aptamer (TBA) in the TT and TGT loop regions by isomeric 2 `-5 `-linkages was found to impose additive destabilizing effects on the thermal stability of the G-quadruplex structure. In contrast, the thermal stability of isomeric 2 `-5 `-linked TBA, i. e., isoTBA, was significantly improved by isomeric 3 `-5 `-phosphodiester linkages. The isoTBA, when modified with 3 `-5 `-linkages in both lateral TT loops (isoTBA202), exhibited higher thermal stability and enzymatic stability in comparison to other oligomers in the present study, and TBA202 showed higher antithrombin activity than other loop-modified TBA oligomers.
Keywords: 2 `-5 `-linked-linked DNA; DNA-isoDNA chimera; isoDNA; loop-modification; thrombin-binding aptamer